Early and Late Haemodynaemic Effects after Adding Fentanyl to Bupivacaine-Lignocaine Mixtures in Supraclavicular Brachial Plexus Block: A Randomized Control Trial - Zainab, Farhanaz (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background Objectives: Haemodynamic changes are very crucial issues during regional anaesthesia. The purpose of the present study was to observe the immediate and late haemodynaemic effects after adding fentanyl to bupivacainelignocaine mixtures in supraclavicular brachial plexus block. Methodology: This randomized clinical study was conducted in the Department of Anesthesiology in Chittagong Medical College Hospital (CMCH) from March 2011 to May 2012 for a period of one year. All patients with the age group of 18 to 65 years who were selected for upper limb surgery distal to the mid arm were the study population. The random allocation of the patient was done into Group A patients (control group) who were received injection Bupivacaine (0.25%) with injection lignocaine A (1%) with injection Normal saline (0.9%). Group B patients (treatment group) were received injection bupivacaine (0.25%) with injection Ligonocaine A (1%) with injection fentanyl. With all aseptic precaution, supraclavicular brachial plexus block was done using paresthesia technique. Pulse and blood pressure were measured at baseline, intra-operatively and post-operatively. Result: A total of 60 patients were enrolled in this study with 30 patients in each group named group A and group B. The mean age of group A and group B were 32.43±12.25 and 34.90±13.05 respectively (p=0.453). The mean pulse rate of group A (79.53±5.03) and group B (78.10±4.26) at baseline level increased at the time of injection (88.30±5.77 and 85.63±4.87 respectively). At 8 hours interval mean pulse rate of group A was 86.47±5.51 compared to that of group B (86.07±3.08). The mean systolic blood pressure of group A (126.50±18.21) and group B (120.07±11.61) at baseline level increased at 0 minute at the time of injection (129.70±15.34 and 123.17±10.57 respectively). The mean diastolic blood pressure of group A (71.73±11.20) and group B (72.73±11.45) at baseline level increased at 0 minute (75.97±12.74 and 75.80±12.85 respectively). At 8 hrs interval mean diastolic pressure of group A was71.73 ±11.20 compared to that of group B (71.73±11.20). Conclusion: In conclusion there is no significant immediate or late haemodynaemic effects after adding fentanyl to bupivacaine-lignocaine mixtures in supraclavicular brachial plexus block. J Bangladesh Coll Phys Surg 2022; 40: 17-22